2018
DOI: 10.1007/s00406-018-0958-3
|View full text |Cite
|
Sign up to set email alerts
|

Adult attention-deficit/hyperactivity disorder, risky substance use and substance use disorders: a follow-up study among young men

Abstract: We investigated whether adult attention-deficit/hyperactivity disorder (ADHD) predicts risky substance use and substance use disorders (SUDs), and its impact on the course of these problematic substance use patterns. Our sample included 4975 Swiss men (mean age 20 ± 1.2 years) who participated in the baseline and 15-month follow-up assessments of the Cohort Study on Substance Use Risk Factors. We examined: (1) the contribution of ADHD, as assessed at baseline, on the risky use of alcohol, nicotine and cannabis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 60 publications
(98 reference statements)
0
5
0
1
Order By: Relevance
“…The observed higher ADHD symptom severity in comorbid individuals in this sample, especially impulsivity, might also resemble a predisposing factor for developing a comorbidity of AUD in ADHD. As proposed in other studies, ADHD individuals are more susceptible to developing AUD (Charach et al, 2011;Estévez-Lamorte et al, 2019;Estévez et al, 2015;Lee et al, 2011;Wilens & Morrison, 2011). Increased impulsivity (Pedersen et al, 2016;Roberts et al, 2014) and decreased inhibitory control (Smith et al, 2014) have been associated with the development of AUD.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The observed higher ADHD symptom severity in comorbid individuals in this sample, especially impulsivity, might also resemble a predisposing factor for developing a comorbidity of AUD in ADHD. As proposed in other studies, ADHD individuals are more susceptible to developing AUD (Charach et al, 2011;Estévez-Lamorte et al, 2019;Estévez et al, 2015;Lee et al, 2011;Wilens & Morrison, 2011). Increased impulsivity (Pedersen et al, 2016;Roberts et al, 2014) and decreased inhibitory control (Smith et al, 2014) have been associated with the development of AUD.…”
Section: Discussionmentioning
confidence: 83%
“…The worldwide prevalence of adult ADHD is estimated to be 2.8% in the general population (Fayyad et al, 2017). ADHD increases the risk for heavy substance use or developing a substance use disorder (SUD), particularly alcohol use disorder (AUD; Charach, Yeung, Climans, & Lillie, 2011;Estévez-Lamorte et al, 2019;Estévez et al, 2015;Lee, Humphreys, Flory, Liu, & Glass, 2011;Vogel et al, 2016;Wilens & Morrison, 2011). Within the AUD population, prevalence of adult ADHD ranges from 7.7% to 21.1%, with a rate of 20.5% in a German sample (Daigre et al, 2015;Luderer et al, 2018;Reyes et al, 2016;Roncero et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molina et al [12] observed an escalation of alcohol, tobacco, cannabis, and illicit drug use throughout adolescence until the age of 21, and a decline in alcohol, tobacco, and cannabis use thereafter. Another study by Estévez-Lamorte et al [50], using the same sample as Vogel et al [30], found that a subsample of the ADHD S+ group showed maturation out of alcohol, nicotine, and CUDs and risky cannabis use. Breyer et al [16] and Levy et al [19] did not observe any change in SUD prevalence rates over time.…”
Section: Discussionmentioning
confidence: 99%
“…Viele Betroffene leiden auch an einer gestörten Affektregulation. Die Erkrankung ist mit einem erhöhten Risiko für verschiedenste psychische Störungen verbunden, insbesondere eine Substanzkonsumstörung (SKS; [8,29]).…”
Section: Adhs Bei Erwachsenen Patienten Mit Substanzkonsumstörungenunclassified